“Bilateral Capnocytophaga Canimorsus Periprosthetic Joint Infections in an Immunocompromised Patient: A Case Report and Literature Review” - Philomena Burger, BA; Mina Botros, MD; Katelyn S. Quartuccio, PharmD, BCIDP; Sonal S. Munsiff, MD; Thomas Myers, MD, MPT (Arthroplasty Today)
A 63-year-old dog owner with bilateral total knee arthroplasties developed periprosthetic joint infections bilaterally due to Capnocytophaga canimorsus (C canimorsus), a bacterium commonly found in the saliva of dogs and cats. Aerobic and anaerobic cultures from explant surgery were negative; however, bacterial 16S polymerase chain reaction followed by sequencing of the amplified product identified C canimorsus in both knees. Treatment was successful with bilateral explant, antibiotic spacers, intravenous antibiotics, and reimplantation. C canimorsus is a rare cause of prostheses infections. As total knee arthroplasty prevalence increases, infections will also increase. Treatment is best provided with collaboration among orthopaedic surgeons, infectious disease specialists, and pharmacists.